2016
DOI: 10.3855/jidc.6661
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of ESBLs among Escherichia coli isolates from outpatients with recurrent UTIs and their antimicrobial resistance

Abstract: Introduction: Extended-spectrum β-lactamase (ESBL)-producing strains of Enterobacteriaceae are considered to be emerging pathogens. They are a major problem in hospitalized as well as community-based patients. Major outbreaks involving ESBL strains have been reported from all over the world. Recurrent urinary tract infection (UTI) is one of the risk factors for infection with ESBL-producing E. coli in hospitalized and non-hospitalized patients. Methodology: Ninety-one E. coli isolates from outpatients with rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…In addition, a similar result was obtained by Alqasim et al [25] in Saudi Arabia who reported that 41% of UPEC isolates were potential ESBL producers, but a higher rate of potential ESBL-producing UPEC was reported by Al-Mayahie et al [26] in Iraq, Thabit et al [27] in Egypt and Mukherjee et al [28] in India, where the rates were 80.2%, 76.47, 70%, respectively. For the ESBL confirmatory double-disk synergy test, DDST detected ESBLs in 42/110 (38.18%).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In addition, a similar result was obtained by Alqasim et al [25] in Saudi Arabia who reported that 41% of UPEC isolates were potential ESBL producers, but a higher rate of potential ESBL-producing UPEC was reported by Al-Mayahie et al [26] in Iraq, Thabit et al [27] in Egypt and Mukherjee et al [28] in India, where the rates were 80.2%, 76.47, 70%, respectively. For the ESBL confirmatory double-disk synergy test, DDST detected ESBLs in 42/110 (38.18%).…”
Section: Discussionsupporting
confidence: 76%
“…Higher levels of ESBL production were reported by Al-Mayahie et al [26] in Iraq, Chandra et al [14] in India, Al-Agamy et al [30] in Egypt, Mekki et al [31] in Sudan, and Abayneh et al [32] in Southwest Ethiopia. The rates reported for each study were 64.8%, 62.5%, 60.9%, 53% and 76.5%, respectively.…”
Section: Discussionmentioning
confidence: 79%
“…From these tables we can observe that studies conducted in non-con ict affected countries appeared to be slightly more focused in terms of site of infection under investigation compared to studies conducted in con ict affected countries, where in a substantial proportion of cases the site of infection was not speci ed, or the authors were analysing resistance pro les of bacteria isolated from a miscellanea of specimens. Publication bias was assessed for a sub-sample of ten studies which presented the proportion of ESBL producers among E. coli isolates on urinary samples, six of which were conducted in con ict-affected countries (45,54,59,75,114,159) and four in non-con ict settings (154,155,164,165). Figure 4 shows the funnel plots elaborated on the logarithm of the proportion of ESBL producers amongst E. coli isolates in urine samples in all studies, and in studies conducted in con ict and non-con ict settings separately.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Recent studies also from Jordan and Middle East Arab region reported high prevalence of MDR E. coli recovered from community and hospitalized patients suffering of UTIs. The rates of MDR E. coli in these studies were ranged between 42% and 87.9% [ 20 , 22 - 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies which had investigated the incidence of CTX-M-types of ESBLs and specifically carbanpenemases among uropathogenic E. coli in the Middle East Arab countries [ 20 , 22 - 24 ]. This study has found high rates of MDR E. coli isolates carried CTX-M-1 (76%) and CTX-M-15 (78%).…”
Section: Discussionmentioning
confidence: 99%